Primary school Physical Education syllabus; draft - Trinidad and Tobago. Ministry of Education (Ministry of Education, 1986)
This draft represents the first phase of the process of developing a new primary school programme of work. It discusses the rationale for the programme, the aims and objectives of physical education at the primary school, and details the programme content for each level.
Keywords: Physical education